KOMODIFIKASI TUBUH PEREMPUAN DALAM IKLAN JUDI ONLINE DI INSTAGRAM - Prasetyo, Angger Prasetyo; Kristiyono, Jokhanan (DIGICOM : Jurnal Komunikasi dan Media, 2024)
This research is motivated by online gambling advertisements on Instagram social media by showing the dominance of female figures as commodification objects. In this advertisement, a female figure is shown wearing a bikini and showing an element of female sensuality, this can lead to gender inequality between men and women. The purpose of this study was to find out how the form of commodification of women occurs in online gambling advertisements on Instagram. This research is a qualitative study using the critical discourse analysis method of the Sara Mills model which has two basic concepts, namely the Position of the Subjects and the Position of the Reader or it can be called the position of the audience. The object to be studied is online gambling advertisements on Instagram social media.The results of the study show that women are often presented as subjects, characters who tell themselves as subjects to attract the audience. This is shown by showing how the female body is used as an object solely to attract men's interest in playing online gambling. The concept of the female body in commodification is a symptom that we often encounter in advertisements, the female body is likened to one of the commodifications that has a selling point. As a commodity, the body that can be converted is the concept of body and physical capital, which can be converted into economic, cultural and social capital.